2014
DOI: 10.1890/13-1912.1
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with under‐ and over‐dispersed count data in life history, spatial, and community ecology

Abstract: Count data arise frequently in ecological analyses, but regularly violate the equi-dispersion constraint imposed by the most popular distribution for analyzing these data, the Poisson distribution. Several approaches for addressing over-dispersion have been developed (e.g., negative binomial distribution), but methods for including both underdispersion and over-dispersion have been largely overlooked. We provide three specific examples drawn from life-history theory, spatial ecology, and community ecology, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 47 publications
2
51
0
Order By: Relevance
“…For the GLMM we used a Conway–Maxwell–Poisson distribution, using function glmmTMB in package glmmTMB (Magnusson et al, ) which can model this distribution, for all metrics except relative species richness and abundance, for which we used a beta distribution as they are proportion data. Compared with other distributions used for analyzing count data, Conway–Maxwell–Poisson distribution has increased model performance because it addresses violations of equi‐dispersion flexibly (Lynch, Thorson, & Shelton, ). In all models, we treated year and treatment as fixed effects, and included their interaction.…”
Section: Methodsmentioning
confidence: 99%
“…For the GLMM we used a Conway–Maxwell–Poisson distribution, using function glmmTMB in package glmmTMB (Magnusson et al, ) which can model this distribution, for all metrics except relative species richness and abundance, for which we used a beta distribution as they are proportion data. Compared with other distributions used for analyzing count data, Conway–Maxwell–Poisson distribution has increased model performance because it addresses violations of equi‐dispersion flexibly (Lynch, Thorson, & Shelton, ). In all models, we treated year and treatment as fixed effects, and included their interaction.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis methods that include likelihood frameworks have been developed for count data (de Valpine and Harmon-Threatt 2013;Fletcher et al 2005;Lynch et al 2014), but this mixture model is explicitly created for proportional data. Formal model selection is standard in other areas such as regression (Burnham and Anderson 1998;Hilborn and Mangel 1997) and is typically done using AIC or likelihood ratio tests.…”
Section: Discussionmentioning
confidence: 99%
“…These constraints often lead to underdispersion where the variance is smaller than the mean (Kendall and Wittmann , Lynch et al. ). In addition, distributions of reproductive effort are often “zero‐inflated”, meaning that there are more zeros observed than would be expected under a given statistical model.…”
Section: Introductionmentioning
confidence: 99%
“…Lynch et al. () subsequently demonstrated that the Conway‐Maxwell‐Poisson (CMP) distribution, which has the same flexibility to model under‐ and overdispersion, is also well‐suited to modeling reproductive data. Although regression models using the GP distribution commonly fail to converge when residuals are underdispersed (Famoye et al.…”
Section: Introductionmentioning
confidence: 99%